Public Debt – Economic Growth Nexus: A Systematic Literature Review - Yangailo, Tryson (Journal of Developing Economies, 2024)
The purpose of this study was to present a systematic literature review on the public debt-economic growth nexus. The objective was to provide policymakers and researchers with significant insights on the impact of public debt on economic growth and to provide reliable evidence on the gaps in the literature that require their urgent attention. The study used a systematic review of the literature contained in two databases, namely Semantic Scholar and Google Scholar. The study shows that public debt above the threshold is detrimental to economic growth, while low public debt is conducive to growth, and that the degree of non-linearity in the debt-growth relationship varies considerably depending on the economic status and debt burden of the country. Policymakers in each country should identify the tipping point at which further public debt begins to impede growth. Debt policy should take into account not only fiscal constraints, but also the effectiveness of governance and the possible consequences of eroding public confidence. The study also shows that institutional quality, public investment, production expenditure, foreign direct investment and exports are among the variables that significantly affect the relationship between public debt and economic growth. Policymakers should control the level of public debt and its drivers to support longer-term economic growth. The study also recommends that countries account for public debt and ensure that such debt is acquired only to finance profitable investments that generate future returns, and not for consumption, deficit reduction, wasteful spending, or political purposes.